2001
DOI: 10.1002/1521-3862(200109)7:5<191::aid-cvde191>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure CVD of Antimony Oxides

Abstract: Semiconducting metal oxides are the key components in one of the most widely exploited forms of generic sensor devices and represent a fast growing sector of the market. [1±4] Tin oxide in particular has been widely studied in this respect, and numerous studies have shown that sensor selectivity can be brought about by the introduction of a second, dopant metal. [5±10] We have recently demonstrated the fabrication of Pt-doped tin oxide by a dual-source CVD approach. [11,12] Other metal oxides that have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The Lewis acidity of the antimony center is expected to be diminished by nitrogen lone pair donation and the extent of this interaction is evidently greater for ½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 SbðOSMe 2 Þ on the basis that the Sb-N bond length [2.265(6) Å ] is much shorter than that in [j 4 …”
mentioning
confidence: 90%
See 3 more Smart Citations
“…The Lewis acidity of the antimony center is expected to be diminished by nitrogen lone pair donation and the extent of this interaction is evidently greater for ½j 4 -NðCH 2 Ar Bu t 2 OÞ 3 SbðOSMe 2 Þ on the basis that the Sb-N bond length [2.265(6) Å ] is much shorter than that in [j 4 …”
mentioning
confidence: 90%
“…PET (e.g. Dacron Ò , Mylar Ò and Terylene Ò ) [1][2][3], and as precursors for the deposition of thin films of Sb 2 O 3 and Sb 6 O 13 [4]. The coordination chemistry of antimony alkoxide and aryloxide compounds is, however, complex, as illustrated by the structural variations that are observed for [Sb(OMe) 3 ] n [5], [Sb(OPr i ) 3 ] 2 [6], [Sb(OSiMe 3 ) 3 ] 2 [7,8], Sb(OC 6 H 3 -2,6-Me 2 ) 3 [9], and [Sb 2 (OCH 2 CH 2 O) 3 ] n [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found that Sb 2 O 3 was easily spread on TiO 2 by heating at elevated temperatures and that the spread Sb 2 O 3 species could be oxidized to Sb 6 O 13 [20]. The decomposition of ( n BuO) 3 Sb on Pyrex glass solids at 650 8C in the absence of O 2 was found to produce Sb 2 O 3 in sebarmonite form, while the decomposition of (EtO) 3 Sb at 700 8C produces Sb 6 O 13 [21].…”
Section: Introductionmentioning
confidence: 99%